Thermo‐Mechanical Analysis of Crack Propagation Process in Heterogeneous Brittle Coal and Its Effects on the UCG Cavity Growth Rate - Mohammadreza Shahbazi; Mehdi Najafi; Mohammad Fatehi Marji; Abolfazl Abdollahipour (Energy Science & Engineering)
ABSTRACT The mechanism of cavity growth in a UCG process is mainly dependent on the presence of fractures and microcracks in the coal seam. In this study, the rate of cavity growth and the crack propagation mechanism in brittle coal samples under high thermal conditions are investigated using a two‐dimensional particle flow code (PFC2D). Coal samples with different cleats' orientation under thermal environments are numerically simulated. The numerical modeling results show that the induced thermal stress is one‐third of the coal sample failure stress. This is due to the increase in particles' volume, the change in normal force between the particles' bonds, and the changes in thermal and mechanical parameters resulting from the applied source temperature, which breaks the bond around the particle. The effects of heat and heterogeneity on the strength of coal samples are also studied under different temperatures ranging from 50°C to 900°C. The results showed that the presence of high‐strength coal seams reduces the formation and propagation of heat‐induced cracks, consequently reducing the cavity growth rate. The soft coal sample has more plasticity, and the cavity growth rate in the soft coal is more than that of the hard coal. The elasticity modulus and uniaxial compressive strength decrease with the increase of the source temperature and the sample begins to deform in a plastic mode. Also, increasing temperature causes an exponential increase in thermal stress. From the fracture mechanics point of view, knowing the conditions and the mechanism of pre‐existing crack propagation in the coal seam can lead to a correct understanding of cavity growth during the UCG process.